“Determinación de la actividad antioxidante de cascarilla de cacao (Theobroma cacao l.) provenientes de las variedades CCN-51 y nacional por distintos métodos” - Coronel Álvarez, Zomayra Judith (2021)
At present, in Ecuador there is an important production and export of cocoa thanks to the excellent quality of the almonds (aroma and unique flavor, nutritional composition), which leads to a greater demand both nationally and internationally. According to various investigations carried out on cocoa, it has been shown that almonds and their derivatives contain a potential source of antioxidants (polyphenols, flavanols, theobromine, caffeine, etc.), which are chemical substances that are characterized by preventing or delaying the oxidation of various substances in the human body. For this reason, the objective of this research was to determine the antioxidant activity of the cocoa husk of the CCN-51 and Nacional varieties by the ABTS, FRAP and ORAC methods. For which the Student's “t” test and Pearson's correlation were used in order to compare the antioxidant content with the antioxidant activity. In the cocoa shell variety CCN-51, values of 626.62, 768.0 and 227.22 μM TE • g-1 were obtained in the ABTS, FRAP and ORAC methods, respectively; while in the National variety, the values obtained were 433.66, 639.51 and 209.87 μM TE • g-1 in the ABTS, FRAP and ORAC methods. The analysis allowed to observe that in the ABTS and FRAP methods there was a positive correlation with Epicatechin, while with Catechin, Caffeine and Theobromine, the correlation was negative. For the ORAC method, the correlation was negative with respect to all the antioxidants evaluated. Keywords: Antioxidant capacity, phytonutrients, free radicals, waste, waste recovery